Pengaruh Promosi dan Lokasi Terhadap Keputusan Pembelian Rumah KPR pada PT. Dzakiyah Mabrukah Gemilang - Afdhol Rinaldi; Khairunnisa Atifah (ISLAMIC BUSINESS and FINANCE (IBF), 2021)
The purpose of this study is to determine how much influence promotion and location have on purchasing decisions at PT. Dzakiyah Mabrukah Gemilang. The population in this study are consumers who buy houses at PT. Dzakiyah Mabrukah Gemilang. The sample used is the entire population of 43 respondents. Data collection methods used are observation, questionnaires (questionnaire), and documentation. Data analysis techniques are descriptive and quantitative. The analytical method used is Multiple Linear Regression using the SPSS 23 program. The results of the t-test research show a significant promotion (0.000) and location (0.002) smaller than 0.05, so that partially significant effect on purchasing decisions. The results of the f test show that 0.000 is significantly smaller than 0.05 so that simultaneously promotion and location have a significant effect on purchasing decisions. The results of multiple linear regression test if promotion and location are constant equal to zero then the value of the purchase decision is 2.396, if the addition of 1 value to the promotion then the value of the purchase decision increases to 0.481 is considered constant, and if the addition of 1 value to the location then the value of the purchase decision increases to 0.342 is considered constant. The result of the coefficient of determination (R2) shows 64.4% that purchasing decisions are influenced by promotion and location, 35.6% purchasing decisions are influenced by other variables not examined in this study. Keywords: Promotion, Location and Purchase Decision